2016
DOI: 10.1134/s0026261716030139
|View full text |Cite
|
Sign up to set email alerts
|

Diversity at low abundance: The phenomenon of the rare bacterial biosphere

Abstract: Rare bacterial biosphere (RBB) is a large and probably predominant sector of bacterial diversity, which is specifically represented by small populations. Although some RBB components have been characterized phenotypically (actualistic objects), it has been mainly described as a set of virtual objects, i.e., of the 16S rRNA gene sequences from environmental DNA samples, which are grouped into phylotypes (operational taxonomic units, OTUs). The upper OTU threshold for RBB is presently not standardized. It is usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 83 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…The principle objectives of this study were to determine how diverse actinobacterial communities are in the Atacama Desert and how big a resource this presents for biotechnology exploitation, and to dissect such diversity in terms of actinobacterial rare and previously undetected dark matter 21 , 22 . To this end, we have applied R H Whittaker’s classic diversity indices 23 to actinobacterial diversity of a hyper-arid—extreme hyper-arid landscape at five distinct habitats covering an altitude range of approximately 900–2500 m absl.…”
Section: Introductionmentioning
confidence: 99%
“…The principle objectives of this study were to determine how diverse actinobacterial communities are in the Atacama Desert and how big a resource this presents for biotechnology exploitation, and to dissect such diversity in terms of actinobacterial rare and previously undetected dark matter 21 , 22 . To this end, we have applied R H Whittaker’s classic diversity indices 23 to actinobacterial diversity of a hyper-arid—extreme hyper-arid landscape at five distinct habitats covering an altitude range of approximately 900–2500 m absl.…”
Section: Introductionmentioning
confidence: 99%
“…The seven sequences were classified into a single OTU (denovo_289). The low relative abundance of P. marinum indicated that it was a rare bacterial species which were regarded as the threshold of five sequences per OTU ( Skopina et al, 2016 ). Thus, it is assumed that P. marinum is present as a rare species in the surface seawater.…”
Section: Resultsmentioning
confidence: 99%
“…An important trait of the rare biosphere is the extremely high diversity, which facilitates their contributions to the entire communities [57] and has been termed the "seed bank" effect [24,25]. Within melt ponds and periglacial rivers, rare sub-communities were significantly more diverse than the dominant sub-communities.…”
Section: The Role Of Rare Sub-communities On the Bacterial Communitiementioning
confidence: 99%
“…Although it has long been known that bacterial species interact with each other to form complicated networks capable of community level functions, such interaction in glacial ecosystems have only been studied very recently [22,23]. Furthermore, modern ecology has recognized the over-proportional role of rare species, especially in pristine environments [24,25]. For instance, it is the rare biosphere that controls the succession strategy and ecological functions of bacterial communities during early periglacial lake ontogeny [26].…”
Section: Introductionmentioning
confidence: 99%